Assessment of nursing students’ knowledge about hysterectomy - Katarzyna Bryńczak; Karolina Blaszka; Emilia Jarosińska; Dominik Olejniczak (Nowotwory)
INTRODUCTION: Hysterectomy is one of the most commonly performed surgical procedures among women worldwide.This study aims to assess nursing students’ knowledge of hysterectomy and their understanding of its impact on patients’ lives. MATERIAL AND METHODS: A diagnostic survey method was employed, using a questionnaire as the primary researchtool. The study group consisted of 102 undergraduate and postgraduate nursing students from four Polish universities. RESULTS: Hysterectomy was correctly defined by 83.3% (n = 85) of respondents; however, 16.7% (n = 17) misidentifiedthe procedure, often confusing it with other gynecological surgeries. CONCLUSIONS: The high percentage of correct responses regarding the definition of hysterectomy indicates a generallygood level of knowledge among nursing students. This suggests that education in this area is effective across the studypopulation.